Animal health and nutrition: metabolic disorders in cattle and improvement strategies - Kang, Danju; Lungu, Shera Elizabeth; Danso, Felix; Dzou, Chrystella Fernanda; Chen, Yanjun; Zheng, Xinyu; Nie, Fanghong; Lin, Hongying; Chen, Jinjun; Zhou, Guangxian (Frontiers in Veterinary Science, 2025)
The health and productivity of cattle are significantly compromised by metabolic diseases on a global scale. These disorders disrupt normal metabolic processes, leading to substantial economic losses for the livestock industry. Metabolic disorders can arise from defective biochemical pathways, deficiencies in enzymes, coenzymes, or cofactors, and may be either inherited or acquired. Dairy cows are particularly susceptible during the transition period from late lactation to early management, facing conditions such as ketosis, milk fever, and hepatic lipidosis. This susceptibility is primarily due to reduced dry matter intake caused by fetal development and a decline in rumen capacity. The negative energy balance (NEB) during this phase, characterized by elevated blood concentrations of non-esterified fatty acids (NEFAs) due to increased energy mobilization, is closely linked to the onset of these diseases. Providing high-energy-density diets during this period is critical to mitigating the effects of NEB. Metabolic disorders represent a major health challenge in cattle, adversely affecting animal welfare and agricultural output. A comprehensive understanding of their etiology, clinical manifestations, diagnostic approaches, and management strategies is essential for effective prevention and treatment. Ongoing research and the adoption of preventive measures are vital to reducing the economic and health impacts of these diseases. Early diagnosis and proactive management strategies are crucial to mitigating their impact on dairy cattle health and productivity. Early identification enables timely interventions, preventing disease progression and reducing adverse effects on animal health. Proactive measures, such as optimizing nutritional programs, implementing precision farming technologies, and ensuring timely veterinary care, are essential for enhancing the overall wellbeing of dairy cows. This review serves as a valuable resource for veterinarians, researchers, and dairy farmers, offering in-depth insights into the etiology, clinical signs, diagnostics, and management of prevalent metabolic disorders in dairy cattle. By equipping stakeholders with this knowledge, it aims to support informed decision-making and improve herd management practices. The focus on early diagnosis and proactive strategies underscores the potential to significantly reduce the economic and health burdens imposed by metabolic diseases on the livestock industry.